Inhibition of GPR91 Reduces Inflammatory Mediators Involved in Active Labor in Myometrium - Ratana Lim; Martha Lappas (Hindawi Limited, 2020)
Problem. Some G-protein-coupled receptors (GPCRs) are regulators of inflammation, yet the role of the GPRC, GPR91, is unknown in human myometrium during the processes of human labor and delivery, a major inflammatory event. Method of Study. GPR91 mRNA expression was assessed using RT-qPCR in myometrium obtained from women at term Caesarean section in the absence of labor and during active spontaneous labor and in a mouse model of inflammation-induced preterm labor. Human primary myometrial cells were used to determine the effect of proinflammatory mediators on GPR91 and the effect of GPR91 siRNA on prolabor mediators. Statistical significance was ascribed to a P<0.05. Results. GPR91 mRNA expression was significantly higher in myometrium from women during term spontaneous labor compared to no labor. Likewise, in mice, GPR91 mRNA expression was significantly upregulated in myometrium during inflammation-induced preterm labor compared to preterm no labor. In myometrial cells, IL1B and TNF significantly increased GPR91 mRNA expression. Knockdown of GPR91 by siRNA in myometrial cells significantly suppressed the secretion and/or expression of IL1B- and TNF-induced proinflammatory cytokines (GM-CSF, IL1A, IL1B, and IL6) and chemokines (CXCL8 and CCL2), myometrial contractility (expression of the contraction-associated proteins PTGFR and CX43, secretion of the uterotonic PGF2α, and in situ collagen gel contraction), and the transcription factor NF-κB. Conclusion. Our findings demonstrate that GPR91 is involved in the genesis of proinflammatory and prolabor mediators induced by IL1B or TNF and collectively suggest that GPR91 may contribute to augmentation of the labor processes.